Um modelo para simulação da avaliação de maturidade nos níveis F e G do MPS.BR com suporte de dinâmica de sistemas. - Freitas, Paulo Ramon Nogueira de (2024)
In today’s society, information systems are essential for companies and individuals. Regardless of the type or specific characteristics, these systems offer significant advantages, such as increased productivity, process optimization and more effective decision making. There is a growing demand for improvements in the enterprise software quality process. In this work, we propose a model to simulate the assessment of maturity levels G and F of the MPS.BR based on Systems Dynamics. Many Organizational Units begin a level assessment in MPS.BR without having a clear idea of how mature their internal processes are or even without knowing these processes. This leads to inaccurate and ineffective assessments. This work proposes the use of a model based on System Dynamics to evaluate the application of maturity levels G and F of the MPS.BR. Through the System Dynamics theory, we propose a Model for applying the maturity assessment of these levels, highlighting the importance of each Expected Result in the Characterization, Aggregation and Maturity of the assessed levels. The research methodology used was Design Science Research (DSR). In the Knowledge Cycle, we carry out a Systematic Literature Review (SLR); in the Design Cycle, we proposed a System Dynamics Model; and in the Relevance Cycle, we carried out a preliminary assessment of the Model with three experts. The result of the study was positive, considering that the Expected Results of each Process, at the two proposed levels, are clearly characterized and aggregated with the proposed Model. In the end, we were able to conclude that the main contribution of this work was to provide a Model to apply the evaluation of levels G and F with Systems Dynamics.